Methodology to nanoencapsulate hepatoprotective components from Picrorhiza kurroa as food supplement. (1st March 2015) - Jia, Dewei; Barwal, Indu; Thakur, Shloka; Yadav, Subhash C.
Abstract: Picrorhiza kurroa root and rhizome powder of extract is well-recognized neutraceutical for healthy liver functioning. The major hepatoprotective components (picrosides I and II) of P. kurroa extract shows poor intestinal absorption and poor bioavailability due to sparingly aqueous solubility. To improve bioavailability of these biomolecules, a nanoformulation of this extract has been developed with pluronic-F-68 copolymer based biodegradable PLA nanoparticles by nanoprecipitation method. This method showed high encapsulation efficiency as 60.1±2.8% (for picroside I) and 67.2±7.4% (for picroside II). The hydrodynamic (by zeta size) and actual size (by TEM) revealed homogenously rounded nanoparticles of size 174±34 nm and 154±12 nm respectively. This formulation showed an initial burst and half release up to 27±3 h, followed by a sustained release (up to 210±10 h). Nanoformulation of this traditional herbal extract provides neutraceutical with value addition property for better hepato-protection by enhancing intestinal absorption and bioavailability.